Uniportal non-coaxial endoscopic posterior cervical discectomy with annular suture repair for C6/C7 disc herniation: a case report - Xiang, Yaoyu; Zhang, Xin; Sun, Fei; Yang, Xianguang; Hu, Xidan; Yang, Jing; Ge, Weiqing; Zhou, Tao; Wang, Yixiao; Song, En (Frontiers in Surgery, 2026)
BackgroundCervical disc herniation with radiculopathy is a common cause of neck and arm pain. While anterior cervical discectomy and fusion (ACDF) remains the standard treatment, it sacrifices motion and may cause adjacent segment degeneration. Uniportal non-coaxial spinal endoscopic surgery (UNSES) offers a motion-preserving alternative. This case presents the first application of UNSES with endoscopic annular suture repair and ligamentum flavum suspension in the cervical spine, demonstrating its technical feasibility.Case presentationA 54-year-old male presented with progressive neck and right right arm pain, numbness and triceps weakness, due to right paracentral C6/C7 disc herniation compressing the C7 nerve root. The patient underwent full-endoscopic posterior cervical discectomy using a uniportal non-coaxial endoscopic system, with ligamentum flavum preservation via suture suspension. The annular defect was repaired intraoperatively using an endoscopic annular suture device under direct visualization. Postoperative imaging confirmed complete neural decompression and successful annular closure without residual disc or dural compromise. Postoperative MRI confirmed complete decompression and annular closure. At 3 months, visual analog scale (VAS) improved from 7 to 1, the Japanese Orthopaedic Association (JOA) score increased from 13 to 16, and the Neck Disability Index (NDI) decreased from 42% to 14%, with no recurrence or instability.ConclusionsUNSES combined with annular suture repair enables safe, motion-preserving decompression for cervical disc herniation. This novel approach may enhance biomechanical integrity, reduce recurrence, and represent a minimally invasive alternative to fusion in selected patients.